A real options approach to implementing corporate social responsibility policies at different stages of the mining process. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to introduce the concept of "optionality" of corporate social responsibility programs in the mining sector. It is postulated that the degree of commitment and implementation varies with the different stages of the mine life cycle.Design/methodology/approach – The methodology/approach applied in this paper follows that of complex systems theory. The authors recognize that elements of CSR do not function/occur in isolation but rather operate in a complex and dynamic system.Findings – The findings presented in the paper indicate that there is a not a single "silver bullet" approach to CSR but rather one that ebbs and flows with not only the technical stage of development of a mine but also those extra‐ economic modifiers that influence a mine's performance and survivability in a competitive global market.Research limitations/implications – The limitations of this particular paper/research is the inability to get a complete set of cost data from any single mining operation. This is due to the highly confidential and proprietary nature of this data, hence a hypothetical/theoretical case is presented.Practical implications – The practical implications of this research include recognizing the different stages of the mine life cycle cause different applications of CSR policy development and implementation. The authors present a view of a flexible and reflective CSR application.Originality/value – This is the first and novel attempt to consider the actual value and commercial implication of CSR using the methods of real options within the broader theoretical framework of complex systems. <ack> <x xml:space="preserve">Acknowledgements</x> Received 25 July 2012 Revised 12 July 2013 Accepted 12 July 2013 </ack>